Assessing Consumer Trust in Ecommerce Strategy for Sustaining the Emerging Commerce Market: A Case of Accra-Tema Metropolis, Ghana - Kwadade-Cudjoe, Francis (British Journal of Marketing Studies, 2025)
ECommerce is an emerging commerce market where organisations and individuals sell and, buy goods and services through the internet using computer and smart devices. This research is to assess the low consumer trust in online trading and how to strengthen it to make consumers confident in eCommerce market. Lack of consumer trust in eCommerce stems from a consumer not receiving neither the goods nor is reimbursed immediately a virtual transaction goes bad, as this negatively impacts his / her trust. Survey design through Questionnaire was employed to collect primary data from the Accra-Tema metropolis in the Greater Accra Region, Ghana, which is popularly noted for intense eCommerce trading activities. Results from the research summarized the effective structure an eCommerce market should have - a certificate of practice and safety measures on the website, standard interface, user friendly website, and an authentic customer feedback system of accountability and equity to build trust that inform purchasing decisions. Furthermore, e-consumers should report problems to e-vendors immediately they occur, and e-vendors must follow up and rectify them ASAP. Finally, transaction problems should immediately be resolved once occurred and reported, e-vendors should encourage e-consumers to continue trading by sending them company and loyalty promotions continuously, and e-consumers should reciprocate / acknowledge the gesture of love from e-vendors for lasting consumer trustworthiness in virtual business transactions.